Acute intestinal infarction caused by initially unexplained splanchnic venous thromboses in a patient with protein C deficiency: A thought-provoking emergency case - Sasaki, Yudai (Int J Surg Case Rep, 2021)
INTRODUCTION AND IMPORTANCE: Splanchnic venous thrombosis (SVT) originating in the superior mesenteric vein (SMV) is rare and may cause acute intestinal infarction (AII). Protein C deficiency (PCD) results in thrombophilia. PRESENTATION OF CASE: Acute unexplained SVT originating in the SMV and portal vein was detected in 68-year-old man. Pan-peritonitis and AII were diagnosed and emergency surgery performed. Part of the small intestine was necrotic and partial resection without anastomotic reconstruction was performed. Heparin was administered intravenously continuously from postoperative day (POD) 1. Hereditary, heterozygous, type 1 PCD was diagnosed postoperatively. The anastomosis was reconstructed on POD 16. Warfarin was substituted for heparin on POD 22. No recurrent thrombosis occurred during 2 years of follow-up. CLINICAL DISCUSSION: Patients with the rare condition of SVT require prompt diagnosis and treatment and may have underlying disease. PCD can cause SVT even in intact veins and anticoagulation therapy should be administered immediately postoperatively. Misdiagnosis and/or delayed treatment of SVT can result in AII, a life-threatening condition with a high mortality rate. Insufficient clinician awareness can result in serious mismanagement of patients with PCD and SVT; emergency patients with AII caused by unexplained SVT should therefore be further investigated for prothrombotic states and assessment of coagulation–fibrinolysis profiles to clarify the underlying mechanism. CONCLUSION: We here present a thought-provoking emergency case of AII associated with acute SVT caused by underlying PCD that was successfully treated by two-stage surgery and anticoagulation therapy. This case provides a timely reminder for emergency clinicians and gastrointestinal surgeons.